Measuring poverty and wellbeing in developing countries - Arndt, Channing; Tarp, Finn, 1951- (Oxford : Oxford University Press, 2017)
This graduate text provides a review of the major approaches employed for estimating poverty lines and how poverty is estimated in practice.
This edition previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on December 8, 2016).
Keywords: Poverty -- Developing countries; Poverty -- Measurement; Well-being -- Developing countries; Well-being -- Measurement